The research of social-design-based maker education: based upon "The old man and the sea" text. Issue 1 (2nd January 2019) - Hung, P. H.; Gao, Y. J.; Lin, R.
ABSTRACT: Since 2015, the Taiwan government has endeavoured to uphold maker education for all-level schools. In addition to "learning by doing" or "learning through play", maker education believed to have varied features that set it apart from preceding pedagogical approaches and have possibility to reform learners' requisite competencies for future. Engaging with "social care" as the mind-set for example, it could drive maker movement towards a value-oriented disposition. This paper discusses the theoretical roots of maker education, collates its beliefs about the whole, and probes the correlation between social design and maker education. We studied how the experimental pedagogy of social-design-based making based on the text of "The Old Man and The Sea" was used at the 2017 New Taipei City Maker Workshop in Taiwan. And we constructed a case study to document its effects within the classroom context. The study revealed that the teaching model of social-design-based maker education would be the sequence as "topic choosing, problem defining, sympathy triggering, conception outputting, prototype making, integrating and sharing", the proportion of teachers'/students' roles in maker courses should be in half of the overall lessons, and teachers' instructions should be concentrated on offering key questions and assisting on integrating learning points mainly.